Regulatory T cell deficiency in patients with eosinophilic asthma. (2nd September 2022) - Sun, Fengfei; Liang, Yingjian; Lin, Minmin; Tan, Cuiyan; Chen, Meizhu; Tu, Changli; Shi, Honglei; Li, Yanlei; Yu, Jinyan; Liu, Jing
Abstract: Background: There is a lack of information about regulatory T cells (Tregs) and inflammatory phenotypes in patients with asthma. In this study, we aimed to compare the characteristics of Tregs in patients with eosinophilic asthma.Methods: Forty healthy and 120 stable asthmatic patients were recruited. Sputum and airway inflammatory phenotypes were assessed, and all patients were followed for one year. Human peripheral blood mononuclear cells (PBMCs) were collected and stimulated with phytohemagglutinin (PHA) and Dermatophagoides farina (Derp) to detect CD4+CD25+FOXP3+T cells and Foxp3 levels. Interleukin (IL)-13, IL-5, IL-17, IL-9, and interferon (IFN)-γ levels were measured.Results: 38.33% of patients had eosinophilic asthma, 13.33% had neutrophilic asthma, 6.67% had mixed granulocytic asthma, and 41.67% had pauci-granulocytic asthma. The eosinophilic asthma patients had a relatively high Asthma Control Test (ACT) score, an increased prediction and improvement FEV1 (%) rate, and elevated total IgE serum levels ( P < 0.05). T helper cell 2 (Th2) cytokines IL-13 and IL-5 were predominantly expressed in the eosinophilic phenotype, while the Th1 cytokine IFN-γ and Th17 cytokine were found in the neutrophilic phenotype. IL-10 was significantly lower in eosinophilic asthmatic patients compared to the controls ( P < 0.05). CD4+CD25+FOXP3+T cells (%Tregs) and Foxp3 gene expression in the PHA stimulated eosinophilic asthma samples were significantly lower compared to the control samples ( P < 0.05). The airway inflammation phenotypes remained stable after one-year of therapy.Conclusion: Asthmatic patients with the eosinophilic phenotype in this study were deficient in Tregs, as characterized by a Th2 cell-biased pattern.